Adsorption and separation of rhenium(VII) using N‐methylimidazolium functionalized strong basic anion exchange resin. Issue 3 (28th August 2012) - Jia, Min; Cui, Hongmin; Jin, Weiqun; Zhu, Lili; Liu, Yu; Chen, Ji
Abstract BACKGROUND: Rhenium is a rare and valuable metal coexisting with molybdenum in molybdenite and sulfide copper ores and is hard to separate. Methods such as solvent extraction, ion exchange, adsorption, precipitation, etc. have been used to separate and purify Re(VII), and resin ion exchange has been widely investigated and used owing to its convenient operation and relatively low‐cost. The main challenge comes from the preparation of resins having high performance and stability. In an earlier study, an N‐methylimidazolium functionalized strong basic anion exchange resin was successfully synthesized and used for Cr(IV) extraction. This paper, reports on further synthesis and application of this resin for adsorption and separation of Re(VII) and Mo(VI), especially from copper arsenic filter cake. RESULTS: At pH 6.25, Re(VII) and Mo(VI) can be effectively separated with the N‐methylimidazolium functionalized strong basic anion exchange resin, giving a Re(VII) recovery of up to 93.3%, but only 5.1% for Mo(VI). When using the copper arsenic filter cake sample 89.1% Re(VII) recovery was achieved. CONCLUSION: The N‐methylimidazolium functionalized strong basic anion exchange resin exhibited high selectivity and recovery for Re(VII) in a mixed system. © 2012 Society of Chemical Industry